2023
DOI: 10.3390/metabo13020260
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS/MS and GC/MS Profiling of Petroselinum sativum Hoffm. and Its Topical Application on Burn Wound Healing and Related Analgesic Potential in Rats

Abstract: Parsley (Petroselinum sativum Hoffm.) is renowned for its ethnomedicinal uses including managing pain, wound, and dermal diseases. We previously highlighted the estrogenic and anti-inflammatory properties of parsley and profiled the phytochemistry of its polyphenolic fraction using HPLC-DAD. To extend our investigation, we here characterized the phytochemical composition of the hydro-ethanolic extract using LC-MS/MS and GC-MS upon silylation, and evaluated the antioxidant, analgesic, antimicrobial, and wound h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…Moreover, other aglycons were characterized along with their glycosidic and acetylated conjugations, such as isorhamnetin, diosmetin, quercetin, and kaempferol. In contrast, different types of polyphenols, mainly oleuropein, arbutin, myricetin, and naringin were recently revealed in the P. sativum hydro-ethanolic extract ( 32 ). The differences in the phytochemical composition are due to many factors, such as the geographical location, climate, soil type, growth stage, cultivation practices, and processing methods.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other aglycons were characterized along with their glycosidic and acetylated conjugations, such as isorhamnetin, diosmetin, quercetin, and kaempferol. In contrast, different types of polyphenols, mainly oleuropein, arbutin, myricetin, and naringin were recently revealed in the P. sativum hydro-ethanolic extract ( 32 ). The differences in the phytochemical composition are due to many factors, such as the geographical location, climate, soil type, growth stage, cultivation practices, and processing methods.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the extract at a 10% concentration in ointment base, specially hydroethanolic extract, showed a significant wound healing activity in a rat model of burn wound. 14 Hexane extract of parsley leaves showed larvicidal activity against Aedes albopictus larva, which suggest it to be a possible promising natural agent to prevent mosquito-borne diseases. 56 Safety Concerns.…”
Section: (Table 2)mentioning
confidence: 98%
“…Figure shows the molecular structures of the main parsley flavonoids. Studies reported the total flavonoid content of parsley within a range of 0.76 mg catechin equivalent per each gram of the dried weight of the hydromethanolic extract to 16.46 mg quercetin equivalent/gram of the hydroethanolic extract of aerial parts. , The most abundant flavonoid present in parsley is apigenin, possessing a trihydroxy-flavone structure, which may be isolated both as an aglycone and as various glycosides. Apiin (apigenin-7- O -apiosyl- O -glucoside), which is the most abundant form of apigenin, as well as cosmosiin (apigenin-7- O -glucoside), are both isolated from the aqueous extract of the leaves .…”
Section: Chemistry Of Parsleymentioning
confidence: 99%
See 2 more Smart Citations